Encephalocraniocutaneous lipomatosis (Haberland syndrome): A rare case report - Ashish Jagati; Bela J Shah; Rima Joshi; Trusha Gajjar (Wolters Kluwer Medknow Publications, 2016)
Haberland syndrome or Fishman syndrome also known as encephalocraniocutaneous lipomatosis (ECCL) is a rare, congenital neurocutaneous disorder. It is characterized by unilateral involvement of skin, eyes and central nervous system. We report the case of a 28-year-old woman who presented with soft lipomatous swelling over right temporal area with nonscarring alopecia of part of frontal and parietal region. The patient had a history of seizures and ipsilateral scleral dermoid. Computed tomography scan findings were suggestive of lipomas and calcification of falx. Magnetic resonance imaging showed right-sided hemi atrophy and two intracranial cysts. We report this case because of its rarity.